THE INFLUENCE OF TEACHER PROFESSIONAL CAPABILITY AND TEACHER EMOTIONAL INTELLIGENCE ON LEARNING PROCESS SD INPRES KAPA KECAMATAN MATTIRO SOMPE PINRANG DISTRICT - A . Tenriningsih (Meraja journal, 2019)
[Full Paper] to pdf Copyright (c) 2018 Meraja journal